Determinación de los niveles de contaminación del agua por la disposición final de residuos sólidos generados en la ciudad de Moyobamba - Ramírez Pérez, Henry Jhonathan (2014)
Thís study was conducted to analyze the quality and rísk of water pollution in Paradise City Moyobamba Sector. In 3 previously established sampling stations were performed. During the months of April to July 3 samples were taken in dry and rainy seasons, in which, nitrates, phosphates, total and fecal coliform, temperature, pH, turbidity, suspended solids, dissolved and total, were measured and then adjusted Quality Index Water (TCA). Population Pollution Tndex (PCT): Using GIS analysis, indicatprs of deterioration in water quality, such as were determined. This was analyzed statistically, with water quality parameters to determine their influence on water pollution. The results indicate that in the Paradise area,·a significant deterioration in water quality does not happen, though, the current land use has a significant participation in it. The total solids, dissolved nutrients and turbidity were the parameters that explained the negative behavior ofthe ICA, as well as vegetation cover and drainage area positively influence. Here, the bottom were more contaminated. Overall, 23% of Sector Paradise presents high vulnerability of deterioration constituent threat of water pollution. Because of this, in the Paradise area a gradual process of deterioration of water quality is evident, according to the disposal of so lid waste deposited in the Municipal dump Moyobamba, such that social marginaJization in access to drinking water is going and not by limitations in quantity, but by altering water quality.